(untitled) (Al-Farooq Journal of Sciences, 2025)
This research addressed the topic of administrative transparency and its impact on organizational excellence within the Ministry of Planning in Tripoli. This research surveyed employees’ opinions on transparency practices in the workplace. The researcher focused on three main dimensions of transparency: the administrative status of procedures and processes, empowering employees to make decisions, and oversight by and for all. The aim was to measure their relationship and impact on achieving organizational excellence. The researcher adopted a descriptive analytical approach and used a questionnaire as the primary tool to collect data from a stratified random sample of ministry employees, spanning various departments and job levels. The results indicated that the level of transparency within the ministry is high, and that employees have a positive perception of the level of organizational excellence, particularly with regard to leadership support and the recruitment of competent personnel. The results of the statistical analysis showed a strong and significant correlation between transparency and organizational excellence, with the overall correlation coefficient reaching (0.859) at a significance level of (0.01). The most influential dimension of transparency on excellence was found to be "oversight by and for everyone," followed by "employee empowerment," while the effect of "administrative status of procedures" was not statistically significant. The transparency model also explains a significant proportion (82.3%) of changes in organizational excellence. The researcher recommended several practical measures to enhance transparency, such as promoting a culture of mutual oversight, empowering employees, reviewing administrative procedures, developing feedback mechanisms, and launching transparent electronic platforms. He also called for designing an internal transparency model, establishing an institutional excellence unit, and linking incentives and promotions to transparency practices. This research forms the basis for developing public administration practices and raising the level of performance in Libyan government institutions.